Mid-estrus uterine blood flow in endometritic and non-endometritic dairy cows using transrectal Doppler ultrasonography. Issue 5 (28th May 2021) - Sharma, Akshay; Singh, Madhumeet; Kumar, Pravesh; Sharma, Isha; Rana, Anchal
ABSTRACT: The objective of the present study was to derive the comparative quantification of various blood flow parameters in endometritic and non-endometritic dairy cows at mid-estrus. Uterine perfusion was investigated by performing the transrectal Doppler ultrasonography of both the middle uterine arteries in Jersey cows diagnosed with clear uterine discharge and clinical endometritis at mid-estrus. Pulsatility and Resistance indices (PI and RI), Time average mean velocity (TAMEAN), Time average maximum velocity (TAMAX), diameter of the artery and volume of blood flow were measured to study the waveforms. Significantly lower ( p < 0.05) PI and RI were found in cows diagnosed with clinical endometritis in comparison to non-endometritic cows. There was significantly higher ( p < 0.01) volume and velocity of blood flow (TAMEAN, TAMAX, Blood flow volume (BFV)-TAMEAN and BFV-TAMAX) in both the middle uterine arteries during endometritis as compared to non-endometritic cows. Also, significantly higher ( p < 0.05) blood flow velocity and volume (TAMEAN, BFV-TAMEAN and BFV-TAMAX) were recorded in middle uterine artery ipsilateral to dominant follicle as compared to contralateral one in non-endometritic cows. The PI value was positively correlated with RI in endometritic ( r = 0.88; p < 0.01) and non-endometritic cows ( r = 0.81; p < 0.01) but negatively correlated with other parameters in all the cows irrespective of inflammatory state of uterus.